Il Regno dell’Imperatore: tipicità e contraddizioni del modello istituzionale giapponese di regolazione dei culti (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Le ragioni di rinnovata attualità di una ricerca storica, religiosa e normativa sulla spiritualità giapponese - 2. Riflessi di natura costituzionale: la costruzione giuridica di un ordinamento nuovo, tra vestigia imperiali e modernità internazionale - 3. Le religioni tradizionali, tra continuità ed elaborazione progressiva - 4. Uno sguardo alle condizioni materiali dei culti di minoranza: problemi e prospettive per un nuovo sincretismo diffuso - 5. I segni di una precisa spiritualità collettiva nel disposto costituzionale e nella legislazione recente: possibili aperture per nuovi studi - 6. Conclusioni in progress: il paradigma nipponico come modello extra-regionale.The Kingdom of the Emperor. Typicality and contradictions in the Japanese institutional paradigm of religious regulationABSTRACT: The history of Japanese legal institutions has probably known in recent years a lack of attention due to the affirmation of other legal paradigms in the same Asian continent. It could seem a plausible underestimation because Japan has usually reached a leading role in the constant evolution of constitutional rules and concrete everyday praxes. An important aspect of this tradition certainly consists in the peculiar Japanese religious approach: a form of customary culture and not only a specific regulation, crossing many spiritual teachings and belongings (Confucianism, Buddhism and Shintoism, with a more recent but truly significant monotheistic nationwide proselytism). The main purpose of this analysis is to notice how this objectively composite religious framework has surprisingly influenced the shape and the implementation of constitutional principles, still offering an interesting overview able to clear up misunderstandings in the intercultural debate between the Western constitutionalism and the Eastern mentality.